2001
DOI: 10.1007/s002130100811
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies of prepulse inhibition models of sensorimotor gating deficits in schizophrenia: a decade in review

Abstract: Studies of drug effects on PPI in rats have generated four distinctive models that have utility in the identification of antipsychotic medications. Because each of these models has specific advantages and disadvantages, the choice of model to be used depends upon the question being addressed. This review should help to guide such decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
1,027
8
22

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 1,413 publications
(1,105 citation statements)
references
References 176 publications
48
1,027
8
22
Order By: Relevance
“…The very robust PPI deficits in the NR1 mutants reproduces findings from several previous studies (Duncan et al, 2006;Fradley et al, 2005) and agree with pharmacological studies that showed a reliable disruption of PPI in rodents and monkeys by NMDAR antagonists (Linn et al, 2003;Geyer et al, 2001). However, it has to be taken into account that these results contrast with most human studies, in which NMDAR antagonists either had no influence or even increased PPI van Berckel et al, 1998;Abel et al, 2003).…”
Section: Habituation and Ppi Of The Startlesupporting
confidence: 90%
See 1 more Smart Citation
“…The very robust PPI deficits in the NR1 mutants reproduces findings from several previous studies (Duncan et al, 2006;Fradley et al, 2005) and agree with pharmacological studies that showed a reliable disruption of PPI in rodents and monkeys by NMDAR antagonists (Linn et al, 2003;Geyer et al, 2001). However, it has to be taken into account that these results contrast with most human studies, in which NMDAR antagonists either had no influence or even increased PPI van Berckel et al, 1998;Abel et al, 2003).…”
Section: Habituation and Ppi Of The Startlesupporting
confidence: 90%
“…Several lines of evidence indicate reduced NMDA receptor (NMDAR) signalling in schizophrenia (Moghaddam, 2003;Javitt and Zukin, 1991) and in particular in the pathophysiology of the observed startle habituation, gating, and AEP generation alterations in schizophrenia (Javitt et al, 2000a;Klamer et al, 2004;Geyer et al, 2001). To provide supporting evidence for this hypothesis we tested a mouse mutant with 90% reduced expression of the NR1 subunit of the NMDA receptor (subsequently named NR1 mutants in this paper) in these paradigms (Mohn et al, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…In addition, the effects of indirect releasers of dopamine, such as amphetamine or cocaine, also appear to disrupt PPI in rats via actions mediated at D 2 -family receptors. Nevertheless, several reports have demonstrated important differences between rat strains in their sensitivity -or insensitivity -to the PPI-disruptive effects of dopamine agonists (Swerdlow et al, 2000;Geyer et al, 2001). Furthermore, recent studies by Swerdlow's group have shown some important differences in the influences of direct D 1 and D 2 agonists in various rat strains, and have even demonstrated the heritability of some of these differences (Swerdlow et al, 2006).…”
Section: The Dopamine Prepulse Inhibition Model In Ratsmentioning
confidence: 99%
“…The neurochemical basis of schizophrenia has been linked to dysfunction in a number of neurotransmitter systems, including the glutamatergic, dopaminergic, and serotonergic systems (for reviews see Laruelle et al, 2003;Geyer et al, 2001;Dean, 2003). However, to date, the exact mechanisms of their role in gating dysfunctions in schizophrenia have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, the exact mechanisms of their role in gating dysfunctions in schizophrenia have not been determined. Animal studies have shown that sensorimotor gating, as measured by PPI, can be modulated by a number of neurotransmitter systems including dopaminergic, glutamatergic, serotonergic, GABAergic, and cholinergic systems (for a review see Geyer et al, 2001). However, these studies have been fairly inconsistent, both in terms of their findings and in the parameters used to measure gating (eg different prepulse intensities and prepulse to pulse intervals in PPI, lack of uniformity across laboratories in P50 peak detection, EEG processing, and filtering and differences in findings using different strains of animals) .…”
Section: Introductionmentioning
confidence: 99%